PENGHAYATAN NILAI PENGORBANAN DALAM EKARISTI MELALUI PELAYANAN MISDINAR (STUDI TERHADAP BUKU-BUKU PANDUAN MISDINAR) - Richard Johanes Rantung; Theresia Vita Prodeita Latief (CREDENDUM: Jurnal Pendidikan Agama, 2026)
This study examines the value of sacrifice in the Eucharist and its relevance to altar server ministry through a study of altar server guidebooks. The problem addressed in this study is the lack of material in altar server guidebooks that explicitly teaches the value of sacrifice in the Eucharist. The scope of this study includes altar server guidebooks, Church documents related to the Eucharist and liturgical ministers, and journal articles relevant to the topic. This study aims to obtain an overview of the content of altar server guidebooks and the extent to which the value of sacrifice in the Eucharist and its relevance to altar server ministry are discussed in these guidebooks. The methodology used in this study is a qualitative method with a literature review. The literature review is a series of activities related to collecting library data, reading, recording, and organizing research materials. The results of this literature review indicate that there is a lack of specific material that systematically helps altar servers develop an appreciation of the value of sacrifice in the Eucharist, particularly in the form of catechesis on the sacrament and Eucharistic ministers. To enable altar servers to emulate Christ's sacrificial spirit, catechetical materials are needed to guide them in recognizing, understanding, and internalizing the value of that sacrifice. The author proposes a catechetical module for altar servers on the theme of the value of sacrifice in the Eucharist. The hope is that these servers will be increasingly able to internalize Christ's sacrifice in the Eucharist through their service.